An investigation in to factors affecting female students' academic success in Ethiopian higher education - Obsa Kebede Wakuma (Springer, 2024)
Abstract The porpuse of this study was to investigate the factors affecting female students' academic success in Ethiopian higher education. To clarify reliable data from the participants, the study used a descriptive survey. The investigation was carried out using a combination of methodologies. One hundred regular undergraduate female students were selected for the sample population using simple random sampling techniques, proportional sampling method, and stratified random sampling because the students were divided into heterogeneous colleges and departments. The methods for gathering data were a questionnaire and concentrated, targeted group discussions. Primary and secondary sources of information were reviewed in order to gather reliable data. The obtained data was sorted, tabulated, and looked for patterns under the distribution of percentages and frequencies using the descriptive method of analysis. The results of this research demonstrate multiple factors influencing female students' academic performance in higher education institutions, including those connected to the institution, families, individuals, and instructors. The conclusions urge the involvement of all stake holders in order to resolve this issue.